Editorial - Corella Parajeles, Juan Pablo (2016)
2016 is a year of great joy for the School of Library Science, Documentation andInformation (EBDI) of the National University.The reason is the celebration of the 20th anniversary Of the Children's Library Miriam Álvarez Brenes (BIMAL), project responsible for collaborating With the development for the taste to the reading and Children's imagination as well as training Integral to fathers and mothers of family.